2015
DOI: 10.1016/j.jinf.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical MRSA isolates from skin and soft tissue infections show increased in vitro production of phenol soluble modulins

Abstract: Summary Background Phenol-soluble modulins (PSMs) are amphipathic, pro-inflammatory proteins secreted by most Staphylococcus aureus isolates. This study tested the hypothesis that in vitro PSM production levels are associated with specific clinical phenotypes. Methods 177 methicillin-resistant S. aureus (MRSA) isolates from infective endocarditis (IE), skin and soft tissue infection (SSTI), and hospital-acquired/ventilator-associated pneumonia (HAP) were matched by geographic origin, then genotyped using sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 44 publications
5
28
1
Order By: Relevance
“…PSMα peptides have also been shown to promote bacterial spread across surfaces (19), destroy neutrophils (5) and erythrocytes (20), and inhibit dendritic cell activity (21) that could potentiate detection by immune response on the skin. Clinically, MRSA isolates from patients with SSTI exhibited higher levels of PSM than MRSA from other distinct clinical syndromes (6). The current study extends this observation into MSSA isolates as well, and provides further evidence for a key role for PSM in the pathogenesis of SSTI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSMα peptides have also been shown to promote bacterial spread across surfaces (19), destroy neutrophils (5) and erythrocytes (20), and inhibit dendritic cell activity (21) that could potentiate detection by immune response on the skin. Clinically, MRSA isolates from patients with SSTI exhibited higher levels of PSM than MRSA from other distinct clinical syndromes (6). The current study extends this observation into MSSA isolates as well, and provides further evidence for a key role for PSM in the pathogenesis of SSTI.…”
Section: Discussionmentioning
confidence: 99%
“…Spa genotyping was performed as previously described (6, 17). The eGenomics online platform (http://tools.egenomics.com) was used to define spa type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4F). Recently, staphylococcal PSMs have been implicated in skin and soft tissue infection (SSTI) (28)(29)(30) and have shown significantly higher levels of expression in methicillin-resistant S. aureus (MRSA) strains isolated from SSTIs. These observations imply that the small ORFs detected in the present study might be candidates that contribute to in vivo abscess formation.…”
Section: Resultsmentioning
confidence: 99%
“…However, reports from mice models concluded that PVL is not a virulence determinant (62). Other reports have reported on the importance of other staphylococcal toxins / virulence determinants such as phenol soluble modulin alpha and alpha-haemolysin (Hla) (cytolytic toxins) (60,63,64). ST93, the Queensland clone is known to encode phenol soluble modulin alpha and alpha-haemolysin as well as PVL (49) and is virulent in animal infection models.…”
Section: Ca-mrsa Virulence Factorsmentioning
confidence: 99%